Tata Bahasa Kasus Fillmore Dalam Cerpen Al-Yatîm Oleh Fatima Mohsen: Tata Bahasa Kasus Fillmore Dalam Cerpen Al-Yatîm Oleh Fatima Mohsen - Hariyani, Nety Novita; Rofidah, Ni’ma; Abyad, Habil; Maula, Siti Zulfa Hidayatul (Language Development Center, 2022)
Background: Case grammar emerged with Fillmore's response to developments in transformation grammar, which has been an interesting subject to syntacticians and semanticists for many decades. Purpose: This study aims to (1) reveal the modalities in the short story Al-Yatîm by Fatima Mohsen; and (2) to describe the propositions in the short story Al-Yatîm by Fatima Mohsen based on the grammar theory of Charles J Fillmore's case. Method: This research includes descriptive-qualitative research. The primary data sources used are quotations from the short story Al-Yatîm by Fatima Mohsen, and the secondary data sources used are books and journals relâted to research studies. The data collection technique in this study was the note-reading technique. The data analysis technique used is Miles and Huberman's data analysis Results and Discussion: The results of this study include: (1) there are 5 types of modality, namely time (madhi, hal, mustaqbal), sign (janib madhi, janib haal, janib mustaqbal), negation (lâ, lâysa, lan), adverb (taroddad, darojah), and mood (irsyadiyah); and (2) there are 8 types of propositional cases, namely agentive case (dhomir ana, dhomir mustatir nahnu, waliid, wahiid, at-tiflu as-shoghir), experiential case (tahmilu), instrument case (jihaz), objective case (zaujatahu, kalâmaha), source case (ta'uda, i'adah, ajro'), purpose case (ilâ at-thobib, ilâ al-mabna), locative case (ma'mal, daaril aytam, maktabil mudiroh), and time case (tsalâsatu asyhur, at-tsanawatil khoms). Conclusions and Implications: Case grammar studies not only focus on English grammar, but can also be applied to all grammatical languages including Arabic. In the grammar of the Fillmore case, each case has a semantic role in the sentence aiming to exp lâ in the relâtionship between the predicate and the noun phrase. With this research, readers are expected to be able to understand the grammar of cases, and be able to apply it in the learning process. Relâted to the suggestion that needs to be looked at for future researchers is to examine more references and other theories related to case grammar, as well as be better prepared in the process of data analysis so that they can get good research results. In addition, researchers understand that this study is far from perfect. Therefore, researchers ask for constructive advice from readers so that in the future they can present better research or other written works.